Novel Strategies and Approaches in Hypertension Therapy - Uzun, Hafize; Atukeren, Pinar, 1975- (Singapore : Bentham Science Publishers, 2019)
Hypertension has become a major public health problem in the last few decades. High blood pressure is a serious risk factor for premature cardiovascular disease and end organ damage including left-ventricular hypertrophy and congestive heart failure, which in-turn increases the risk of cardiovascular morbidity and mortality. While studies of hypertension have been performed worldwide in a variety of epidemiological settings such as diabetes, renal function, obesity and thyroid disorders, there is a need to identify appropriate treatment strategies Novel Strategies and Approaches in Hypertensio.
Novel Strategies and Approaches in Hypertension Therapy
Print version record.
eBooks on EBSCOhost
Keywords: Hypertension -- Treatment; Hypertension artérielle -- Traitement; Cardiology; MEDICAL; Hypertension -- Treatment